2023
DOI: 10.1158/1078-0432.ccr-22-2807
|View full text |Cite
|
Sign up to set email alerts
|

Phase II Investigation of TVB-2640 (Denifanstat) with Bevacizumab in Patients with First Relapse High-Grade Astrocytoma

Abstract: Purpose: Glioblastoma (GBM) represents the most common primary brain tumor. Although anti-angiogenics are employed in the recurrent setting, they do not prolong survival. GBM is known to upregulate fatty acid synthase (FASN) to facilitate lipid biosynthesis. TVB-2640, a FASN inhibitor, impairs this activity. Patients and Methods: We conducted a prospective, single-center, open-label, unblinded, phase II study of TVB-2640 plus bevacizumab in patients with recurrent high-grade astrocytoma. Patients were randomiz… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(8 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…TVB-2640 advanced to clinical trials for advanced solid tumours, including breast, colon, and ovarian cancer [72]. Notably, in recent Phase 2 clinical studies, TVB-2640 paired with bevacizumab in high-grade astrocytoma demonstrated minimal adverse effects and excellent patient tolerability [73].…”
Section: Increased Fatty Acid Synthesismentioning
confidence: 99%
“…TVB-2640 advanced to clinical trials for advanced solid tumours, including breast, colon, and ovarian cancer [72]. Notably, in recent Phase 2 clinical studies, TVB-2640 paired with bevacizumab in high-grade astrocytoma demonstrated minimal adverse effects and excellent patient tolerability [73].…”
Section: Increased Fatty Acid Synthesismentioning
confidence: 99%
“…Specifically, they preferentially utilize short-chain FAs to facilitate its absorption and acquire a growth advantage when compared to normal brain cells [ 78 , 84 ]. Supporting the critical role of FASN in the carcinogenesis of brain tumors, a recent phase II clinical study of relapsed high-grade astrocytoma showed an objective response rate of 56%, complete response rate of 17%, plus partial response rate of 39% in patients receiving FASN inhibition in combination with bevacizumab [ 85 ]. Progression-free survival at 6 months (PFS6) with the combination of FASN inhibition and bevacizumab was 31.4%, which was statistically significant when compared with historical controls of bevacizumab as monotherapy (BELOB trial; PFS6: 16%) [ 86 ].…”
Section: A New Strategy Of Tailored Therapy For Radioresistant Brain ...mentioning
confidence: 99%
“…Treating glioma stem cells with cerulenin resulted in the inhibition of migration and proliferation of the cells [69]. In a clinical study on patients of first-relapse GBM, co-administration of the FASN inhibitor TVB-2640 and bevacizumab significantly improved the progression-free survival at 6 months compared with bevacizumab treatment alone [70]. A further clinical trial is ongoing to investigate the effect of the oral, selective small-molecule inhibitor of FASN, ASC40 and bevacizumab (Table 1).…”
Section: De Novo Lipogenesismentioning
confidence: 99%